Kinetic Studies of Wastewater Purification Using Local Sand Samples in Erbil, Kurdistan - Hanna, Aveen M; Shareef, Kafia M; Satar, Lathetha O (Iraqi Journal of Science, 2022)
This research describes a straightforward procedure for extracting the pigment of Methylene Blue (MB) dye from aqueous solutions by utilizing a low-cost, safe, natural, and national source. Batch adsorption experiments were carried out to determine contact time, adsorbent dose, and the starting concentration of the adsorbate. For the analysis, a UV spectrophotometer was employed. Dye adsorption equilibrium was obtained after 120 minutes of contact time. Temkin, Langmuir, and Freundlich isotherm adsorption were used at solution concentrations of (3, 4, 6, and 8) mg/l. Adsorption data is used to predict the pseudo first and pseudo second order kinetic equations, Elovich kinetic models, and intra-particle diffusion using pseudo first and pseudo second order kinetic equations. The Langmuir adsorption model fits the MB adsorption data better than other isotherm models, with the MB capacity at 8 mg/l equal to 0.992 mg/g. The pseudo-second-order model and the adsorption kinetic data are satisfactorily related.